2020
DOI: 10.1136/heartjnl-2019-315942
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmic risk stratification in non-ischaemic dilated cardiomyopathy beyond ejection fraction

Abstract: Sudden cardiac death and arrhythmia-related events in patients with non-ischaemic dilated cardiomyopathy (NICM) have been significantly reduced over the last couple of decades as a result of evidence-based pharmacological and non-pharmacological therapeutic strategies. Nevertheless, the arrhythmic stratification in patients with NICM remains extremely challenging, and the simple indication based on left ventricular ejection fraction appears to be insufficient. Therefore, clinicians need to go beyond the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
1
16
0
1
Order By: Relevance
“…Indeed, ICD implantation was an independent prognostic factor for all the three main outcomes considered. Our results highlight the overall prognostic value of ICD implantation in a highly selected DCM population, in line with the results of recent studies 20,21 . The last two periods of enrolment showed comparable outcomes when overall survival as well as heart failure‐related events were considered in the analysis, supporting the importance of reducing fatal arrhythmic events in this population.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, ICD implantation was an independent prognostic factor for all the three main outcomes considered. Our results highlight the overall prognostic value of ICD implantation in a highly selected DCM population, in line with the results of recent studies 20,21 . The last two periods of enrolment showed comparable outcomes when overall survival as well as heart failure‐related events were considered in the analysis, supporting the importance of reducing fatal arrhythmic events in this population.…”
Section: Discussionsupporting
confidence: 89%
“…It is a well-recognized parameter for predicting arrhythmic events, mortality, and LVRR in patients with DCM. 27,28 Furthermore, a wide QRS duration was reported to be associated with diffuse myocardial fibrosis on CMR. 28 QRS duration may reflect the severity of LV dysfunction in addition to conduction abnormalities.…”
Section: The Left Ventricular Reverse Remodelling Predicting Scorementioning
confidence: 99%
“…Life-threatening arrhythmias occur during the first 6 months after a diagnosis of DCM in approximately 2% of unprotected patients, and 70% of these arrhythmias occur in the first 90 days. 27 An ICD is recommended in patients with DCM, symptomatic heart failure (NYHA class II-III), or an LVEF ≤35% despite ≥3 months of treatment with optimal medical therapy. 30 However, LVRR typically begins after 6 months, to be completed for 12 to 24 months.…”
Section: The Usefulness Of the Left Ventricular Reverse Remodelling Predicting Score For Treatment Strategymentioning
confidence: 99%
“…The AMAZFIT ® for AF was found to have a sensitivity of 93.28%, a specificity of 95.35%, a PPV of 93.28%, an NPV of 95.35%, a PLR 20.06 and an NLR 0.07. Rajakariar et al ( 23 ) reported sensitivity and specificity using the Kardia Band for identifying AF was 94.4 and 81.9% respectively, with positive and negative predictive values of 54.8 and 98.4%, respectively. These findings indicate that the AMAZFIT ® has excellent sensitivity and specificity for the detection of an irregular pulse from AF.…”
Section: Discussionmentioning
confidence: 99%